2022
DOI: 10.1001/jamaneurol.2022.0067
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Consensus Approach to Evaluation of Neonatal Hypotonia in the Genomic Era: A Review

Abstract: he presentation of primary hypotonia in the neonatal intensive care unit (NICU) is complex to diagnose. Although our understanding of the genetic basis of hypotonia has advanced significantly in the past decade, 1-5 there remains a lag in implementation of state-of-the-art genetic testing along with variation in diagnostic approaches across institutions. Availability of effective treatments for genetic conditions, such as congenital myasthenic syndromes or spinal muscular atrophy (SMA), [6][7][8] highlights th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…Short stature is one indicator of a potential genetic condition, as are other nonspecific features, such as hypotonia, for which genome-wide sequencing has also been proposed as the ideal first-line diagnostic tool. 14 Rather, these data provide further support of genome-wide testing as a first-tier test for anyone suspected to have a rare genetic condition.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Short stature is one indicator of a potential genetic condition, as are other nonspecific features, such as hypotonia, for which genome-wide sequencing has also been proposed as the ideal first-line diagnostic tool. 14 Rather, these data provide further support of genome-wide testing as a first-tier test for anyone suspected to have a rare genetic condition.…”
mentioning
confidence: 79%
“…Thus, while Li et al present a thorough and rigorous systematic review and meta-analysis evaluating the yield of 2 standard genetic tests for a particular clinical feature, and genetic testing for short stature is recognized to have potential benefits, the nonspecific nature of short stature makes it difficult to infer widespread conclusions from these data. Short stature is one indicator of a potential genetic condition, as are other nonspecific features, such as hypotonia, for which genome-wide sequencing has also been proposed as the ideal first-line diagnostic tool . Rather, these data provide further support of genome-wide testing as a first-tier test for anyone suspected to have a rare genetic condition.…”
mentioning
confidence: 99%
“…25 IPCHiP institutions included: Murdoch Children's Research Institute/Royal Children's Hospital (Melbourne, Australia), The Hospital for Sick Children (SickKids®; Toronto, Ontario, Canada), University College London/Greater Ormond Street Hospital (London, United Kingdom), and Boston Children's Hospital (Massachusetts, USA). 26,27 At the suggestion of the original study team members, additional expertise was sought in: (i) neuropsychological assessment and cognitive phenotyping (via Seaver Autism Center for Research and Treatment; New York, USA), [28][29][30] and (ii) adult phenotyping (via University Health Network; Toronto, Ontario, Canada). 31,32 Authors J.C., L.D., P.G., T.L., P.S., Z.S., J.A.S.V., C.D., N.J., D.B.…”
Section: Development Of Phenotype Reporting Guidelines Through a Modi...mentioning
confidence: 99%
“…Certain patient characteristics, such as neurological signs or symptoms, or multiple congenital anomalies, are associated with increased rates of molecular diagnosis. Several multicenter studies in different countries have demonstrated the reproducible benefit of ES/GS in children with explicit phenotypic criteria for diagnosis and clinical decision making ( 24 , 62 , 63 ).…”
Section: Advances In Diagnostic Genetic Testing For Newbornsmentioning
confidence: 99%
“…ES is able to detect uniparental disomy and deletions which could be an alternative cause of imprinting disorders. Therefore, many centers consider targeted testing for triplet repeat disorders and methylation disorders and rapid chromosomal microarray in conjunction with ES for internal exon deletions ( 62 ).…”
Section: Advances In Diagnostic Genetic Testing For Newbornsmentioning
confidence: 99%